1996
DOI: 10.2535/ofaj1936.73.1_25
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin in the Cestodes, Taenia solium and Taenia hydatigena

Abstract: The demonstration of prolactin in cestodes, Taenia solium and Taenia hydatigena, was investigated by using immunocytochemical method. PRL immunoreactivity was widely distributed in the CNS and PNS in the worms. In the scolex PRL-IR perikarya occurred in the cerebral ganglia, around the basic area of the sucker and the rostral border region between the rostellum and the suckers with strong immunoreaction, distinctly in Taenia solium. A number of PRL-IR nerve fibres were observed in the main nerve cords, and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The existence of prolactin immunoreactive nerve cell bodies and fibres on the surface of the main excretory duct was observed in our previous study (Liu et al, 1996). 5-HT, peptide histidine isloeucine and histoaminergic immunoreactive cell bodies and fibres were also demonstrated in the wall of the ducts (Gustafsson et al, 1986and Wikgren et al, 1990).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The existence of prolactin immunoreactive nerve cell bodies and fibres on the surface of the main excretory duct was observed in our previous study (Liu et al, 1996). 5-HT, peptide histidine isloeucine and histoaminergic immunoreactive cell bodies and fibres were also demonstrated in the wall of the ducts (Gustafsson et al, 1986and Wikgren et al, 1990).…”
Section: Discussionsupporting
confidence: 64%
“…The present study, however, has offered some additional data to contribute to the detailed distribution, besides nervous system, accumulation of positive perikarya and processes was observed between the longitudinal and transverse muscle layers, forming intermuscular nerve plexes and extending their processes to the musculature organs. It is interesting that a number of neurosecretory elements in the scolex were stained with aldehyde-fuchsin, which was obtained also in PRL immunocytochemical staining in some area in our previous study (Liu et al , 1996). Moreover, they showed almost similar shape, size and localization which the cells located individually or in group.…”
Section: Discussionmentioning
confidence: 54%
“…Ishikawa et al (1987) reported that the cultured stellate cells of rat anterior pituitary secrete S-100 protein which stimulates release of prolactin. In our previous research prolactin immunoreactivity was also found in the cerebral ganglia and ganglionated transverse commissure (Liu et al, 1996). Whether there is a functional relation between S-100 protein and prolactin needs further study.…”
mentioning
confidence: 79%
“…Quintanar et al (2007a) found PRL in larval stages of the nematode Trichinella spiralis, in the nervous and reproductive systems of cestodes: Ligula intestinalis (Liu et al 1995), Taenia solium and Taenia hydatigena (Liu et al 1996), and it has been found in granules of neurons in insects: Leucophaena maderae (Veenstra et al 1985), Apis mellifera (Schmid et al 1990), Locusta migratoria and Sarcophaga bullata (Swinnen et al 1990).…”
mentioning
confidence: 99%